USAGE EFFICIENCY CURRENT ASSETS IN ENTERPRISES - Mavlyanova Dilobar Makhkamovna (Scholar Express Journals, 2022)
The article discusses the existing methods of asset analysis, approaches to the analysis of current assets, presents the shortcomings of the existing methodology, proposes the author's methodology for the analysis of current assets, summarizes the existing methods, as well as adds new coefficients and clarifies the main directions of the analysis of current assets. The analysis of such an element of current assets as accounts receivable and cash is considered. In an analysis of individual elements of current assets, the structure of current assets are proposed and their influence on the final financial result is substantiated
Keywords: Current Assets; The Efficiency Of Using Current Assets; Stages Of Analysis Of Current Assets; Coefficients Of Current